Zn-coated samarium-iron-nitrogen magnetic sheet and preparation method thereof
By coating samarium-iron nitrogen magnetic powder and adding a rubber layer, the problems of poor magnetic properties and easy oxidation of samarium-iron nitrogen magnets are solved, the demand for high-performance flexible magnetic materials is achieved, and the service life is extended.
Patent Information
- Application Number
- CN202411994092.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The magnetic properties of samarium-iron nitrogen magnets are poor and easy to oxidize, resulting in reduced performance and shortened service life, which cannot meet the needs of high-performance flexible sheet magnetic materials.
Zn coats samarium nitrogen magnetic powder and adds a rubber layer to the outer layer. A double-layer coating process is adopted to improve the oxidation resistance and magnetic properties of the magnet.
It achieves good magnetic properties and oxidation resistance of samarium-iron nitrogen magnetic sheets, extends its service life, and meets the needs of high-performance flexible magnetic materials.
Smart Images

Figure CN119764039A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials, and in particular relates to a Zn-coated SmFeN magnetic sheet and a preparation method thereof. Background Art
[0002] As the fourth generation of permanent magnet material, samarium iron nitride has good temperature stability, high Curie temperature, better intrinsic magnetism, and excellent magnetic properties. It has been widely used in instruments, microwave communication technology, electric motors and other equipment, and is one of the research hotspots of rare earth permanent magnet materials.
[0003] However, the problem of easy oxidation of SmFeN powder has never been solved; and the demand for high-performance flexible sheet magnetic materials in application fields such as high-end furniture and home appliances, aerospace, electric vehicles, and wireless charging is increasing, and rigid SmFeN blocks can no longer meet market demand.
[0004] SmFeN rubber magnets can be formed by mixing SmFeN magnetic powder with a rubber matrix. The rubber matrix makes the magnet soft and bendable, so that it can be used on curved or irregular surfaces or in situations where shock absorption is required.
[0005] At present, the preparation of flexible SmFeN magnets mainly involves mixing magnetic powder with rubber and then rolling it into shape. However, this method has the following technical problems: the bonding strength between the magnetic powder and the matrix material is low, and the magnetic powder is easy to fall off the surface of the magnet; the magnetic powder in the magnet has poor antioxidant ability, which leads to reduced performance of the magnet and shortened service life, thus limiting the application and development of flexible SmFeN magnets. Summary of the invention
[0006] The object of the present invention is to provide a Zn-coated SmFeN magnetic sheet to solve the problem of poor magnetic properties of the SmFeN magnetic sheet.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A Zn-coated SmFeN magnetic sheet comprises a Zn-coated SmFeN magnet matrix and a rubber layer, that is, a double-layer coating, wherein the inner coating layer is Zn and the outer coating layer is a rubber layer;
[0009] The Zn-coated SmFeN magnet matrix comprises Zn-coated SmFeN magnetic powder, a binder, an optional processing aid and an optional lubricant;
[0010] The rubber layer includes rubber and an adhesive.
[0011] Furthermore, the Zn-coated SmFeN magnetic powder includes SmFeN powder and Zn powder;
[0012] The samarium iron nitrogen powder is prepared by Ca reduction nitriding ball milling;
[0013] The particle size of the samarium iron nitrogen powder is 10-50 μm, preferably 20-30 μm.
[0014] Furthermore, the binder is selected from at least one of polyurethane, thermosetting phenolic epoxy resin, polyester, polystyrene, polyamide and polyethylene, preferably thermosetting phenolic epoxy resin.
[0015] Furthermore, the processing aids are dispersants and plasticizers;
[0016] The dispersant is one of phosphate amine and triethanolamine, preferably triethanolamine;
[0017] The plasticizer is a phthalate plasticizer, a terephthalate plasticizer, a benzoate plasticizer, preferably a phthalate plasticizer;
[0018] The lubricant is at least one of polyethylene wax, ultra-low molecular weight polyethylene, stearic acid lubricant, polymer wax and oligomer wax, preferably polyethylene wax.
[0019] Furthermore, the rubber is selected from at least one of hydrogenated nitrile rubber, isoprene rubber and isoprene rubber, preferably isoprene rubber.
[0020] Another object of the present invention is achieved by the following technical solution: A method for preparing a Zn-coated samarium iron nitrogen magnetic sheet, comprising the following steps:
[0021] (1) Preparation of Zn-coated SmFeN magnetic powder:
[0022] Grinding the SmFeN powder and Zn powder for 30-60 minutes to obtain a mixed powder; placing the mixed powder in a quartz boat and placing it in a tube furnace, sintering at 450°C-620°C for 6-10 hours, introducing nitrogen as a protective gas during sintering, and obtaining Zn-coated SmFeN magnetic powder;
[0023] (2) Preparation of Zn-coated SmFeN magnet matrix:
[0024] Smelting the Zn-coated SmFeN magnetic powder, binder, optional processing aid and optional lubricant obtained in step (1) to obtain a Zn-coated SmFeN magnet matrix;
[0025] (3) Preparation of rubber layer:
[0026] Melting the rubber and the binder to obtain a rubber layer;
[0027] (4) Preparation of Zn-coated SmFeN magnetic sheets:
[0028] The Zn-coated SmFeN magnet matrix obtained in step (2) and the rubber layer obtained in step (3) are melted and calendered to obtain a Zn-coated SmFeN magnetic sheet.
[0029] Furthermore, in step (1), the mass ratio of SmFeN powder to Zn powder is 9:1-3.
[0030] Furthermore, in step (2), the mass of the adhesive accounts for 7-20% of the mass of the Zn-coated SmFeN magnetic powder, preferably 10-15%;
[0031] In step (2), the mass of the processing aid accounts for 1-5% of the mass of the Zn-coated SmFeN magnetic powder, preferably 2-4%; the lubricant accounts for 1%-5% of the mass of the Zn-coated SmFeN magnetic powder, preferably 1%;
[0032] The smelting temperature in step (2) is 140-280° C., preferably 150-170° C.; the smelting time is 0.2-1 h, preferably 0.5-0.9 h.
[0033] Furthermore, in step (3), the mass of the adhesive accounts for 5-15% of the mass of the rubber, preferably 6-8%;
[0034] The smelting temperature in step (3) is 150-240° C., preferably 180-210° C.; the smelting time is 0.3-1 h, preferably 0.3-0.6 h.
[0035] Furthermore, in step (4), the mass ratio of the rubber layer to the Zn-coated SmFeN magnet matrix is 1:5-20, preferably 1:12-15;
[0036] In step (4), the elongation of the Zn-coated SmFeN magnet matrix is 60-75%, and the tensile strength is 2.5-3 MPa;
[0037] The calendering pressure in step (4) is 6 MPa;
[0038] The smelting temperature in step (4) is 140-280°C, preferably 150-170°C; the smelting time is 0.2-1h, preferably 0.5-0.9h.
[0039] Beneficial effects of the present invention:
[0040] (1) The present invention first uses Zn powder to coat SmFeN powder, and uses the low-melting-point Zn element under N2 gas as a protective gas to coat the SmFeN powder by high-temperature sintering in a tubular furnace to obtain Zn-coated SmFeN magnetic powder; and then coats it with a rubber layer and calenders it to obtain a Zn-coated SmFeN magnetic sheet.
[0041] (2) The Zn-coated SmFeN magnetic sheet prepared by the double-layer anti-oxidation treatment method of the present invention has good magnetic properties, which provides a new method for the coating process of SmFeN magnets. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The present invention will be further described below in conjunction with the accompanying drawings.
[0043] Figure 1 1 is a hysteresis loop diagram of the samarium iron nitrogen magnetic sheets prepared in the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0044] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] This embodiment provides a Zn-coated SmFeN magnetic sheet, which is prepared by the following steps:
[0047] (1) Preparation of Zn-coated SmFeN magnetic powder:
[0048] SmFeN powder and Zn powder were mixed in a mass ratio of 9:2 and ground for 40 minutes to obtain mixed powder; the mixed powder was placed in a quartz boat and placed in a tube furnace, and sintered at 550°C for 8 hours, and nitrogen was introduced as a protective gas during sintering to obtain Zn-coated SmFeN magnetic powder;
[0049] (2) Preparation of Zn-coated SmFeN magnet matrix:
[0050] The Zn-coated SmFeN magnetic powder obtained in step (1), thermosetting phenolic epoxy resin, triethanolamine, dibutyl phthalate and polyethylene wax are melted at 160° C. for 40 min to obtain a Zn-coated SmFeN magnet matrix; the thermosetting phenolic epoxy resin, triethanolamine, dibutyl phthalate and polyethylene wax account for 12%, 2%, 2% and 1% of the mass of the Zn-coated SmFeN magnetic powder, respectively;
[0051] (3) Preparation of rubber layer:
[0052] The isoprene rubber and F48 thermosetting phenolic epoxy resin are melted at 180°C for 0.5h to obtain a rubber layer; the F48 thermosetting phenolic epoxy resin accounts for 8% of the mass of the isoprene rubber;
[0053] (4) Preparation of Zn-coated SmFeN magnetic sheets:
[0054] The Zn-coated SmFeN magnet matrix obtained in step (2) and the rubber layer obtained in step (3) are melted at 160°C for 40 minutes and rolled at 6MPa to obtain a Zn-coated SmFeN magnet sheet; the mass ratio of the rubber layer to the Zn-coated SmFeN magnet matrix is 1:9.
[0055] Example 2
[0056] This embodiment provides a Zn-coated SmFeN magnetic sheet, which is prepared by the following steps:
[0057] (1) Preparation of Zn-coated SmFeN magnetic powder:
[0058] SmFeN powder and Zn powder were mixed in a mass ratio of 9:2 and ground for 40 minutes to obtain mixed powder; the mixed powder was placed in a quartz boat and placed in a tube furnace, and sintered at 550°C for 8 hours, and nitrogen was introduced as a protective gas during sintering to obtain Zn-coated SmFeN magnetic powder;
[0059] (2) Preparation of Zn-coated SmFeN magnet matrix:
[0060] The Zn-coated SmFeN magnetic powder obtained in step (1), thermosetting phenolic epoxy resin, triethanolamine, dibutyl phthalate and polyethylene wax are melted at 160° C. for 40 min to obtain a Zn-coated SmFeN magnet matrix; the thermosetting phenolic epoxy resin, triethanolamine, dibutyl phthalate and polyethylene wax account for 12%, 2%, 2% and 1% of the mass of the Zn-coated SmFeN magnetic powder, respectively;
[0061] (3) Preparation of rubber layer:
[0062] The isoprene rubber and F48 thermosetting phenolic epoxy resin are melted at 180°C for 0.5h to obtain a rubber layer; the F48 thermosetting phenolic epoxy resin accounts for 8% of the mass of the isoprene rubber;
[0063] (4) Preparation of Zn-coated SmFeN magnetic sheets:
[0064] The Zn-coated SmFeN magnet matrix obtained in step (2) and the rubber layer obtained in step (3) are melted at 160°C for 40 minutes and rolled at 6MPa to obtain a Zn-coated SmFeN magnet sheet; the mass ratio of the rubber layer to the Zn-coated SmFeN magnet matrix is 1:10.
[0065] Example 3
[0066] This embodiment provides a Zn-coated SmFeN magnetic sheet, which is prepared by the following steps:
[0067] (1) Preparation of Zn-coated SmFeN magnetic powder:
[0068] SmFeN powder and Zn powder were mixed in a mass ratio of 9:2 and ground for 40 minutes to obtain mixed powder; the mixed powder was placed in a quartz boat and placed in a tube furnace, and sintered at 550°C for 8 hours, and nitrogen was introduced as a protective gas during sintering to obtain Zn-coated SmFeN magnetic powder;
[0069] (2) Preparation of Zn-coated SmFeN magnet matrix:
[0070] The Zn-coated SmFeN magnetic powder obtained in step (1), thermosetting phenolic epoxy resin, triethanolamine, dibutyl phthalate and polyethylene wax are melted at 160° C. for 40 min to obtain a Zn-coated SmFeN magnet matrix; the thermosetting phenolic epoxy resin, triethanolamine, dibutyl phthalate and polyethylene wax account for 12%, 2%, 2% and 1% of the mass of the Zn-coated SmFeN magnetic powder, respectively;
[0071] (3) Preparation of rubber layer:
[0072] The isoprene rubber and F48 thermosetting phenolic epoxy resin are melted at 180°C for 0.5h to obtain a rubber layer; the F48 thermosetting phenolic epoxy resin accounts for 8% of the mass of the isoprene rubber;
[0073] (4) Preparation of Zn-coated SmFeN magnetic sheets:
[0074] The Zn-coated SmFeN magnet matrix obtained in step (2) and the rubber layer obtained in step (3) are melted at 160°C for 40 minutes and rolled at 6MPa to obtain a Zn-coated SmFeN magnet sheet; the mass ratio of the rubber layer to the Zn-coated SmFeN magnet matrix is 1:12.
[0075] Example 4
[0076] This embodiment provides a Zn-coated SmFeN magnetic sheet, which is prepared by the following steps:
[0077] (1) Preparation of Zn-coated SmFeN magnetic powder:
[0078] SmFeN powder and Zn powder were mixed in a mass ratio of 9:2 and ground for 40 minutes to obtain mixed powder; the mixed powder was placed in a quartz boat and placed in a tube furnace, and sintered at 550°C for 8 hours, and nitrogen was introduced as a protective gas during sintering to obtain Zn-coated SmFeN magnetic powder;
[0079] (2) Preparation of Zn-coated SmFeN magnet matrix:
[0080] The Zn-coated SmFeN magnetic powder obtained in step (1), thermosetting phenolic epoxy resin, triethanolamine, dibutyl phthalate and polyethylene wax are melted at 160° C. for 40 min to obtain a Zn-coated SmFeN magnet matrix; the thermosetting phenolic epoxy resin, triethanolamine, dibutyl phthalate and polyethylene wax account for 12%, 2%, 2% and 1% of the mass of the Zn-coated SmFeN magnetic powder, respectively;
[0081] (3) Preparation of rubber layer:
[0082] The isoprene rubber and F48 thermosetting phenolic epoxy resin are melted at 180°C for 0.5h to obtain a rubber layer; the F48 thermosetting phenolic epoxy resin accounts for 8% of the mass of the isoprene rubber;
[0083] (4) Preparation of Zn-coated SmFeN magnetic sheets:
[0084] The Zn-coated SmFeN magnet matrix obtained in step (2) and the rubber layer obtained in step (3) are melted at 160°C for 40 minutes and rolled at 6MPa to obtain a Zn-coated SmFeN magnet sheet; the mass ratio of the rubber layer to the Zn-coated SmFeN magnet matrix is 1:13.
[0085] Comparative Example 1
[0086] This comparative example provides a Zn-coated SmFeN magnetic sheet, which is prepared by the following steps:
[0087] (1) Preparation of Zn-coated SmFeN magnetic powder:
[0088] SmFeN powder and Zn powder were mixed in a mass ratio of 9:2 and ground for 40 minutes to obtain mixed powder; the mixed powder was placed in a quartz boat and placed in a tube furnace, and sintered at 550°C for 8 hours, and nitrogen was introduced as a protective gas during sintering to obtain Zn-coated SmFeN magnetic powder;
[0089] (2) Preparation of Zn-coated SmFeN magnet matrix:
[0090] The Zn-coated SmFeN magnetic powder obtained in step (1), thermosetting phenolic epoxy resin, triethanolamine, dibutyl phthalate and polyethylene wax are melted at 160° C. for 40 min to obtain a Zn-coated SmFeN magnet matrix; the thermosetting phenolic epoxy resin, triethanolamine, dibutyl phthalate and polyethylene wax account for 12%, 2%, 2% and 1% of the mass of the Zn-coated SmFeN magnetic powder, respectively;
[0091] (3) Preparation of rubber layer:
[0092] The isoprene rubber and F48 thermosetting phenolic epoxy resin are melted at 180°C for 0.5h to obtain a rubber layer; the F48 thermosetting phenolic epoxy resin accounts for 8% of the mass of the isoprene rubber;
[0093] (4) Preparation of Zn-coated SmFeN magnetic sheets:
[0094] The Zn-coated SmFeN magnet matrix obtained in step (2) and the rubber layer obtained in step (3) are melted at 280°C for 40 minutes and rolled at 6MPa to obtain a Zn-coated SmFeN magnet sheet; the mass ratio of the rubber layer to the Zn-coated SmFeN magnet matrix is 1:9.
[0095] Comparative Example 2
[0096] This comparative example provides a samarium iron nitrogen magnetic sheet, which is prepared by the following steps:
[0097] (1) Preparation of samarium iron nitrogen magnet matrix:
[0098] SmFeN powder, thermosetting phenolic epoxy resin, triethanolamine, dibutyl phthalate and polyethylene wax are melted at 160°C for 40 minutes to obtain a SmFeN magnet matrix; the thermosetting phenolic epoxy resin, triethanolamine, dibutyl phthalate and polyethylene wax account for 12%, 2%, 2% and 1% of the mass of the SmFeN powder respectively;
[0099] (2) Preparation of rubber layer:
[0100] The isoprene rubber and F48 thermosetting phenolic epoxy resin are melted at 180°C for 0.5h to obtain a rubber layer; the F48 thermosetting phenolic epoxy resin accounts for 8% of the mass of the isoprene rubber;
[0101] (3) Preparation of SmFeN magnetic sheets:
[0102] The samarium iron nitrogen magnet matrix obtained in step (1) and the rubber layer obtained in step (2) are melted at 160° C. for 40 minutes and calendered at 6 MPa to obtain a samarium iron nitrogen magnetic sheet; the mass ratio of the rubber layer to the samarium iron nitrogen magnet matrix is 1:9.
[0103] The performance of the samarium iron nitride magnetic sheets prepared in Examples 1 to 4 and Comparative Examples 1 to 2 was tested. Figure 1 It is the hysteresis loop diagram of SmFeN magnetic sheet;
[0104] Depend on Figure 1 It can be seen that the Zn-coated SmFeN magnetic sheets prepared in Examples 1 to 4 have higher coercivity, indicating higher magnetic properties. Meanwhile, Zn coating and rubber coating are beneficial to improving their oxidation resistance and extending their service life.
[0105] Comparative Example 1 increases the melting temperature of the Zn-coated SmFeN magnet matrix and the rubber layer, and the obtained SmFeN magnetic sheet has a lower coercive force, indicating that it has poor magnetic properties. The reason is that the melting point of Zn is low, and too high a melting temperature will affect the mixed coating of the SmFeN magnetic sheet and destroy the Zn coating layer; Compared with Example 1, Comparative Example 2 does not perform Zn coating on the SmFeN powder, but only performs rubber coating. The obtained SmFeN magnetic sheet has a lower coercive force, indicating that it has poor magnetic properties. Therefore, simultaneously coating the SmFeN magnetic sheet with Zn and rubber is beneficial to improving the magnetic properties of the SmFeN magnetic sheet.
[0106] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0107] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A Zn-coated SmFeN magnetic sheet, characterized in that: It includes a Zn-coated samarium iron nitrogen magnet matrix and a rubber layer, that is, it has a double-layer coating, an inner coating layer is Zn, and an outer coating layer is a rubber layer; The Zn-coated SmFeN magnet matrix comprises Zn-coated SmFeN magnetic powder, a binder, an optional processing aid and an optional lubricant; The rubber layer includes rubber and an adhesive.
2. The Zn-coated SmFeN magnetic sheet according to claim 1, characterized in that: The Zn-coated SmFeN magnetic powder comprises SmFeN powder and Zn powder; The samarium iron nitrogen powder is prepared by Ca reduction nitriding ball milling; The particle size of the samarium iron nitrogen powder is 10-50 μm, preferably 20-30 μm.
3. The Zn-coated SmFeN magnetic sheet according to claim 1, characterized in that: The binder is selected from at least one of polyurethane, thermosetting phenolic epoxy resin, polyester, polystyrene, polyamide and polyethylene, preferably thermosetting phenolic epoxy resin.
4. The Zn-coated SmFeN magnetic sheet according to claim 1, characterized in that: The processing aids are dispersants and plasticizers; The dispersant is one of phosphate amine and triethanolamine, preferably triethanolamine; The plasticizer is a phthalate plasticizer, a terephthalate plasticizer, a benzoate plasticizer, preferably a phthalate plasticizer; The lubricant is at least one of polyethylene wax, ultra-low molecular weight polyethylene, stearic acid lubricant, polymer wax and oligomer wax, preferably polyethylene wax.
5. The Zn-coated SmFeN magnetic sheet according to claim 1, characterized in that: The rubber is selected from at least one of hydrogenated nitrile rubber, isoprene rubber and isoprene rubber, preferably isoprene rubber.
6. The method for preparing a Zn-coated SmFeN magnetic sheet according to any one of claims 1 to 5, characterized in that: The steps include: (1) Preparation of Zn-coated SmFeN magnetic powder: Grinding the SmFeN powder and Zn powder for 30-60 minutes to obtain a mixed powder; placing the mixed powder in a quartz boat and placing it in a tube furnace, sintering at 450°C-620°C for 6-10 hours, introducing nitrogen as a protective gas during sintering, and obtaining Zn-coated SmFeN magnetic powder; (2) Preparation of Zn-coated SmFeN magnet matrix: Smelting the Zn-coated SmFeN magnetic powder, binder, optional processing aid and optional lubricant obtained in step (1) to obtain a Zn-coated SmFeN magnet matrix; (3) Preparation of rubber layer: Melting the rubber and the binder to obtain a rubber layer; (4) Preparation of Zn-coated SmFeN magnetic sheets: The Zn-coated SmFeN magnet matrix obtained in step (2) and the rubber layer obtained in step (3) are melted and calendered to obtain a Zn-coated SmFeN magnetic sheet.
7. The method for preparing a Zn-coated SmFeN magnetic sheet according to claim 6, characterized in that: In step (1), the mass ratio of SmFeN powder to Zn powder is 9:1-3.
8. The method for preparing a Zn-coated SmFeN magnetic sheet according to claim 6, characterized in that: In step (2), the mass of the adhesive accounts for 7-20% of the mass of the Zn-coated SmFeN magnetic powder, preferably 10-15%; In step (2), the mass of the processing aid accounts for 1-5% of the mass of the Zn-coated SmFeN magnetic powder, preferably 2-4%; the lubricant accounts for 1%-5% of the mass of the Zn-coated SmFeN magnetic powder, preferably 1%; The smelting temperature in step (2) is 140-280° C., preferably 150-170° C.; the smelting time is 0.2-1 h, preferably 0.5-0.9 h.
9. The method for preparing a Zn-coated SmFeN magnetic sheet according to claim 6, characterized in that: In step (3), the mass of the adhesive accounts for 5-15% of the mass of the rubber, preferably 6-8%; The smelting temperature in step (3) is 150-240° C., preferably 180-210° C.; the smelting time is 0.3-1 h, preferably 0.3-0.6 h.
10. The method for preparing a Zn-coated SmFeN magnetic sheet according to claim 6, characterized in that: In step (4), the mass ratio of the rubber layer to the Zn-coated SmFeN magnet matrix is 1:5-20, preferably 1:12-15; In step (4), the elongation of the Zn-coated SmFeN magnet matrix is 60-75%, and the tensile strength is 2.5-3 MPa; The calendering pressure in step (4) is 6 MPa; The smelting temperature in step (4) is 140-280°C, preferably 150-170°C; the smelting time is 0.2-1h, preferably 0.5-0.9h.
Citation Information
Patent Citations
Rust-proof sealing material and preparation method thereof
CN101602879A
Halogen-free flame-retardant anti-UV and high-bonding-strength PA encapsulating material and preparation method thereof
CN107434913A
Samarium-iron-nitrogen or neodymium-iron-nitrogen anisotropic bonded magnetic powder and preparation method thereof
CN111411325A
Flexible samarium-iron-nitrogen magnetic material as well as preparation method and application thereof
CN116344140A
Composite magnetic powder and preparation method and application thereof
CN116525235A
Cited By
High-filling high-fluidity high-strength samarium-iron-nitrogen / polyethylene composite material and preparation method thereof
CN121054344A
A high-filler, high-flowability, high-strength samarium iron nitrogen / polyethylene composite material and its preparation method
CN121054344B